2021
DOI: 10.1097/aog.0000000000004276
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring Equitable Implementation of Telemedicine in Perinatal Care

Abstract: Telemedicine in perinatal care has the potential to reduce disparities in maternal and perinatal health outcomes if implemented in an equitable manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…This suggests that barriers to telemedicine access disproportionately affected Black patients seeking care during the pandemic, leading to a greater reliance on in‐person visits than other groups. We hypothesize that technology‐associated disparities including access to video‐enabled devices and digital literacy may drive lower telemedicine use, 15 supported by our results that Black patients were significantly less likely to have an activated patient portal and email addresses on record relative to White patients. Finally, possible mistrust of the health care system and technology in Black communities may contribute to lower rates of telemedicine use 3 , 14 and may influence patients of color to prefer in‐person medical visits, especially if meeting with a new provider.…”
Section: Discussionsupporting
confidence: 53%
“…This suggests that barriers to telemedicine access disproportionately affected Black patients seeking care during the pandemic, leading to a greater reliance on in‐person visits than other groups. We hypothesize that technology‐associated disparities including access to video‐enabled devices and digital literacy may drive lower telemedicine use, 15 supported by our results that Black patients were significantly less likely to have an activated patient portal and email addresses on record relative to White patients. Finally, possible mistrust of the health care system and technology in Black communities may contribute to lower rates of telemedicine use 3 , 14 and may influence patients of color to prefer in‐person medical visits, especially if meeting with a new provider.…”
Section: Discussionsupporting
confidence: 53%
“…As regards telehealth (vs in-person check-ups), our data aligns with previous studies showing that it has been rapidly adopted in perinatal care since the onset of the pandemic (36)(37)(38)(39). Telehealth offers safe access to consultation and follow-up appointments, saving patients both time and money, but is a complex system that normally requires years of implementation and optimization (40) in order to be an effective tool for providing comprehensive and multidisciplinary perinatal care, mainly in cases where physical examination is not or is rarely necessary.…”
Section: Discussionsupporting
confidence: 90%
“…For example, many women in this study mentioned positive aspects of avoiding the full glucose tolerance test. This, in conjunction with the previously mentioned study suggesting the safety of telehealth, provides a basis for cautious research to begin into how telehealth can best be incorporated more fully into the maternity care system, ideally in a manner that avoids the exacerbation of health disparities, especially for low income women ( Fernandez Turienzo et al, 2021 ; Palmer et al, 2021 ; Ukoha et al, 2021 ; Westwood, 2021 ). Another key consideration will be ensuring that telehealth services are of high quality and can adequately maintain the relationship between patient or client and provider, which previous research (as well as data from our study) has suggested to be integral to a positive pregnancy and birth experience ( Hildingsson et al, 2019 ; Lewis, 2019 ).…”
Section: Discussionmentioning
confidence: 73%